2002
DOI: 10.1002/1521-396x(200208)192:2<237::aid-pssa237>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

High-Power III-Nitride Emitters for Solid-State Lighting

Abstract: High‐power, large‐area InGaN/GaN quantum‐well heterostructure light‐emitting diodes based on an inverted, or “flip‐chip”, configuration are described. These devices are mounted in specially designed high‐power (≈1–5 W) packages and exhibit high extraction efficiency and low operating voltage. In the blue wavelength regime, output powers greater than 250 mW (1 × 1 mm2 device) and 1 W (2 × 2 mm2 device) are delivered at standard operating current densities (≈50 A/cm2), corresponding to “wall‐plug” efficiencies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Such high CRI compares favorably to conventional white light sources such as "cool white" fluorescent (CRI ) 62), incandescent (CRI ) 100), and dyeenhanced InGaN/GaN solid-state LEDs (CRI > 80). 25 The peak EQE of our monochrome QD-LEDs are measured to be 1.6% at 4.6 V (0.29 mA/cm 2 ) for red devices, 0.65% at 5.2 V (0.63 mA/cm 2 ) for green, and 0.35% at 9.1 V for blue (1.73 mA/cm 2 ) ( Figure 3). These values are consistent with previously reported QD-LEDs, 2-6 with our green and blue QD-LEDs more efficient than those in previous reports.…”
mentioning
confidence: 99%
“…Such high CRI compares favorably to conventional white light sources such as "cool white" fluorescent (CRI ) 62), incandescent (CRI ) 100), and dyeenhanced InGaN/GaN solid-state LEDs (CRI > 80). 25 The peak EQE of our monochrome QD-LEDs are measured to be 1.6% at 4.6 V (0.29 mA/cm 2 ) for red devices, 0.65% at 5.2 V (0.63 mA/cm 2 ) for green, and 0.35% at 9.1 V for blue (1.73 mA/cm 2 ) ( Figure 3). These values are consistent with previously reported QD-LEDs, 2-6 with our green and blue QD-LEDs more efficient than those in previous reports.…”
mentioning
confidence: 99%
“…17 Another investigation reported that the CCT changed with viewing angle for YAG downconverted white light. 19,20 To further investigate, samples were prepared with only green (GR10) and red (GR01) phosphors in the PMMA host. Both samples exhibited spectral changes with diode power (not shown here).…”
Section: Luminescence Spectramentioning
confidence: 99%
“…As shown in Fig. 1(b), the conformal coating technology was first proposed by Lumileds in the pursuit of the precise control of shape, thickness and particle content of phosphor layer [21], [22]. The remote phosphor structure meaning a physical separation of LED chip and phosphor layer was first proposed in 1995 in order to realize improved lifetime and higher luminous efficacy by reducing backscattering and thermal effect caused by LED chip [23], [24], as depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%